2016
DOI: 10.1099/ijsem.0.000827
|View full text |Cite
|
Sign up to set email alerts
|

Saccharothrix stipae sp. nov., an actinomycete isolated from the rhizosphere of Stipa grandis

Abstract: An actinomycete, strain D34T , was isolated from a soil sample collected from the rhizosphere T (98.6 %). The strain contained meso-diaminopimelic acid, alanine, glycine and glutamic acid as major cell-wall amino acids. Mannose, rhamnose and galactose were the characteristic whole-cell sugars. The fatty acid profile consisted predominantly of iso-C 15 : 0 , iso-C 16 : 0 , iso-C 16 : 1 , C 17 : 1 v6c, anteiso-C 17 : 0 and anteiso-C 15 : 0 . The phospholipid profile included phosphatidylethanolamine (typical of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The genus Saccharothrix belongs to the family Pseudonocardiaceae and was described for the first time by Labeda et al [1]. Since then, Saccharothrix had been found in a variety of environmental components including sediment sample [2], soil [3], endophyte [4] and lake [5]. At the time of writing, LPSN [6] had listed 21 species with validly published names (https://lpsn.dsmz.de/genus/saccharothrix), including the recently described Saccharothrix deserti [7].…”
Section: Full-textmentioning
confidence: 99%
“…The genus Saccharothrix belongs to the family Pseudonocardiaceae and was described for the first time by Labeda et al [1]. Since then, Saccharothrix had been found in a variety of environmental components including sediment sample [2], soil [3], endophyte [4] and lake [5]. At the time of writing, LPSN [6] had listed 21 species with validly published names (https://lpsn.dsmz.de/genus/saccharothrix), including the recently described Saccharothrix deserti [7].…”
Section: Full-textmentioning
confidence: 99%
“…Several Saccharothrix species have been described in the past few years. Saccharothrix stipae (18) and Saccharothrix deserti (19) isolated from the soil collected from northwest China where the study revealed that the strain is aerobic, Gram-positive mesophilic actinobacteria that is identified by 16S rRNA and the S. stipae strain contains major meso-diaminopimelic acid and major amino acids are alanine, glycine, glutamic acid, and mannose, rhamnose and galactose were specified by analysis of whole-cell sugars. S. deserti strain cell wall hydrolysates contained mesodiaminopimelic acid, galactose, and mannose.…”
Section: The Genus Saccharothrixmentioning
confidence: 99%